Enhancing Students’ Vocabulary Mastery through AI-Based Quizizz: A Classroom Action Research at SMA Budi Agung Medan - Utami, Ajeng Galuh Sri; Swondo, Ashari P.; Maisaroh, Enni; Prayoga, Kiymas; Chaerani, Intan (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to improve students' vocabulary mastery in descriptive texts through Artificial Intelligence (AI) Based Quizizz, a gamified and interactive learning tool. It addresses the challenge of low vocabulary retention and aims to boost engagement and motivation in English learning.Method – Using a Classroom Action Research (CAR) design, the study was conducted in two cycles with tenth-grade students at SMA Budi Agung Medan. Data were collected through vocabulary tests, observation sheets, and interviews. Quantitative data were analyzed descriptively, while qualitative data were examined thematically to assess changes in students’ attitudes, motivation, and participation.Findings – The integration of AI based Quizizz led to significant improvements in students’ vocabulary mastery and active engagement. The game-based features and real-time feedback created a student-centered learning environment, enhancing vocabulary retention and motivation. Research Implications – This study underscores the potential of AI-driven gamification tools like Quizizz in enhancing English learning. It suggests further research on its use in other language skills and its long-term impact on motivation and performance.